Impact of the internet usage in academic performance among the UiTM student in Samarahan / Nursyamsina Sopian Khan, Noor Marlinie Rajuna and Cathrine Boni - Sopian Khan, Nursyamsina; Rajuna, Noor Marlinie; Boni, Cathrine (2011)
UiTM have provided the wireless connection of internet for the student to access the internet. The student can access by typing the link and get connected to the internet through the access of the UiTM website. The wireless internet connection that has been provided* by UiTM gives various types of impact in bad and good terms towards the student. The information that they gain from the help of the internet can be used to gain some understanding towards any of their findings which they wish to know about. The study on the research that we are being carrying out is to investigate on the impact that the student gets on surfing the internet. It is important to know the impact of the new technology on the student’s academic when these kind of technology that have been upgraded from time to time to make the life much easier.